Eksplorasi Pengalaman Sensorik, Afektif, Sosial, Dan Intelektual Wisatawan Di Petak Enam Glodok, Jakarta - Lukas Gavrila Jefferson; Wiwik Sari (Journal of Innovation Research and Knowledge, 2026)
Petak Enam Glodok is a culinary tourism destination that combines food, history, and Chinese cultural heritage in Jakarta's Chinatown. This study aims to explore tourists' experiences at Petak Enam Glodok through four dimensions: sensory, affective, social interaction, and intellectual experiences. A qualitative approach with a phenomenological method was employed. Data were collected through observation, semi-structured interviews with 30 tourists, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that tourists' sensory experiences were shaped by the taste, aroma, food presentation, and the unique atmosphere that blends heritage and modern concepts. Affective experiences were reflected in feelings of happiness, comfort, enthusiasm, and nostalgia while visiting the destination. Social experiences emerged through positive interactions with friends, family, food vendors, and other visitors, enriching the overall travel experience. Meanwhile, intellectual experiences developed through increased knowledge of Glodok's history, Chinese culture, and cultural heritage. The study concludes that tourist experiences at Petak Enam Glodok are influenced not only by culinary quality but also by the integration of culture, history, atmosphere, and social interaction, creating a memorable tourism experience.